2001
DOI: 10.1182/blood.v98.5.1424
|View full text |Cite
|
Sign up to set email alerts
|

Localized reduction of atherosclerosis in von Willebrand factor–deficient mice

Abstract: To examine the role of the platelet adhesion molecule von Willebrand factor (vWf) in atherogenesis, vWf-deficient mice (vWf؊/؊) were bred with mice lacking the low-density lipoprotein receptor (LDLR؊/؊) on a C57BL/6J background. LDLR؊/؊vWf؉/؉ and LDLR؊/؊vWf؊/؊ mice were placed on a diet rich in saturated fat and cholesterol for different lengths of time. The atherogenic diet stimulated leukocyte rolling in the mesenteric venules in both genotypes, indicating an increase in P-selectin-mediated adhesion to the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
153
1
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(168 citation statements)
references
References 39 publications
(47 reference statements)
6
153
1
4
Order By: Relevance
“…Several adhesion-related molecules were differentially regulated by flow type, including von Willebrand factor, CD44, fibronectin 1, several integrins, cadherins, and junction plakoglobin. The up-regulation of von Willebrand factor (24) and CD44 (25) in particular may have implications for atherogenesis. However, VCAM-1, intercellular adhesion molecule 1, E-selectin, and P-selectin, all associated with early NF-B-mediated inflammatory responses and the onset of atherogenesis, were not detected as differentially expressed despite the increased transcriptional levels of proinflammatory cytokines and NF-B pathway components noted above.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several adhesion-related molecules were differentially regulated by flow type, including von Willebrand factor, CD44, fibronectin 1, several integrins, cadherins, and junction plakoglobin. The up-regulation of von Willebrand factor (24) and CD44 (25) in particular may have implications for atherogenesis. However, VCAM-1, intercellular adhesion molecule 1, E-selectin, and P-selectin, all associated with early NF-B-mediated inflammatory responses and the onset of atherogenesis, were not detected as differentially expressed despite the increased transcriptional levels of proinflammatory cytokines and NF-B pathway components noted above.…”
Section: Resultsmentioning
confidence: 99%
“…Because this is the first in vivo study profiling regional endothelial gene expression on a large scale, we have attempted to bridge the findings to published candidate gene studies in vivo (21)(22)(23)(24) and experiments of flow disturbance in vitro (8,15,16,19,23). Furthermore, we have presented specific observations relating to some pathways that are central to atherogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both endothelial cell P-selectin and von Willebrand factor become the target for platelet GP1b (Theilmeier et al, 2002). A study using mice deficient of von Willebrand factor showed some level of protection from atherosclerosis thus elucidated the role of von Willebrand factor on plaque formation and progression in intact endothelial cells (Methia et al, 2001). …”
Section: Rolling and Adhering Of Platelet To Endothelial Cell Surfacementioning
confidence: 99%